2010
DOI: 10.1177/0269215510380825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exercise training on cardiac baroreflex sensitivity in patients with coronary artery disease: a randomized controlled trial

Abstract: The results suggest that long-term exercise training leads to beneficial effects on baroreflex activity and cardiorespiratory performance in coronary patients, and thus could constitute an efficient nonpharmacological intervention in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
(87 reference statements)
0
23
0
Order By: Relevance
“…It also has been reported that home-based exercise training programs are beneficial in maintaining exercise capacity and reducing healthcare costs in low-risk patients after MI. 236, 237 There has been increasing evidence from largescale epidemiological studies and RCTs on the safety of exercise training and the role of comprehensive programs for elderly patients with cardiovascular diseases. 228,238-241 Elderly patients should be strongly encouraged to participate in cardiac rehabilitation programs.…”
Section: Table 30 Characteristics Of Elderly Patients With Acute Myomentioning
confidence: 99%
“…It also has been reported that home-based exercise training programs are beneficial in maintaining exercise capacity and reducing healthcare costs in low-risk patients after MI. 236, 237 There has been increasing evidence from largescale epidemiological studies and RCTs on the safety of exercise training and the role of comprehensive programs for elderly patients with cardiovascular diseases. 228,238-241 Elderly patients should be strongly encouraged to participate in cardiac rehabilitation programs.…”
Section: Table 30 Characteristics Of Elderly Patients With Acute Myomentioning
confidence: 99%
“…9 Studies have also shown that baroreflex sensitivity was improved following long-term chronic exercise training in a diseased population. 10,11 However, to date no study has examined the effects of short-term exercise on arterial stiffness, limb blood flow and baroreflex sensitivity in young FH þ men. Thus, the purpose of this study was to examine the effects of 4 weeks of moderate intensity aerobic exercise on peripheral and central vascular variables, which include AIx, forearm and leg blood flow (LBF), and baroreflex sensitivity in normotensive young FH þ men.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the benefits of regular exercise on autonomic regulation have been supported by a growing number of studies, showing similar improvements in HRV indexes in time and frequency domain after physical training in healthy elderly, cardiac, hypertensive, diabetic patients on HD and RT …”
Section: Discussionmentioning
confidence: 88%
“…In fact, the benefits of regular exercise on autonomic regulation have been supported by a growing number of studies, showing similar improvements in HRV indexes in time and frequency domain after physical training in healthy elderly, cardiac, hypertensive, diabetic patients on HD and RT. 13,[15][16][17] The vagal modulation observed in the AG group may be due to increased sensitivity of muscarinic acetylcholine receptors, responsible for the activation of cholinergic pathway. 18 Positive adjustment of the baroreflex mechanism was found in the physical exercise intervention group in a study conducted by Kouidi et al, 14 suggesting that these changes may lead to better cardiovascular prognosis of renal transplant.…”
Section: Discussionmentioning
confidence: 99%